20. ACCURACY OF SONOGRAPHIC FETAL WEIGHT ESTIMATION USING THE HADLOCK III FORMULA AT THE NATIONAL HOSPITAL OF OBSTETRICS AND GYNECOLOGY (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to evaluate the accuracy of the Hadlock III formula in estimating fetal weight at the National Hospital of Obstetrics and Gynecology, Hanoi, Vietnam.Methods: A cross-sectional study was conducted on 268 singleton term pregnancies (37–41 weeks) at the National Hospital of Obstetrics and Gynecology. Estimated fetal weight (EFW) was calculated using the Hadlock III formula based on biparietal diameter, head circumference, and femur length. Actual birth weight was measured immediately after delivery. Accuracy was assessed using mean percentage error (MPE), absolute percentage error (APE), and the prediction accuracy rate (APE ≤10%). Agreement was evaluated using Bland-Altman plots and Spearman correlation.Results: The mean percentage error was –0.47%, and the prediction accuracy rate was 82.4%. Bland-Altman analysis showed a mean bias of 50.96g with 95% limits of agreement from –460.99g to 562.91g. Accuracy was reduced in birth weight extremes (4000g). No significant associations were found with maternal age, parity, gestational age, or fetal sex. A significant negative correlation was observed between birth weight and MPE (ρ = –0.351, p < 0.001).Conclusion: The Hadlock III formula demonstrated high accuracy in fetal weight estimation among term pregnancies in a Vietnamese population and is a reliable tool in routine obstetric practice, particularly in settings where abdominal circumference measurement is limited.
Keywords: Fetal weight estimation; Hadlock III; ultrasound; accuracy; birth weight